Numerical analysis and experimental tests for solder joints power cycling optimization. Issue 9 (August 2015) - Cova, P.; Delmonte, N.; Chiozzi, D.
Abstract: Power cycling is the most realistic stress test for thermo-mechanical accelerated failure mechanisms in power devices. The fast evolution in solder materials and packaging techniques makes it necessary to find the proper accelerate test conditions for any specific package/mounting solution. This paper deals with a procedure for determining the power cycling optimal parameters (power rating, period, duty-cycle, cooling conditions) for accelerated stress tests on solder joints of SMD power devices mounted on a specific board. The procedure is based on FEM numerical analysis and preliminary experimental tests. Simulation results are presented; they are validated by comparison with measurements performed using an ad-hoc experimental setup. Early power cycling is also shown.